IMPLEMENTASI PEMBIASAAN SALAT DUHA DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA DI MTsN 9 JAKARTA - Nur Humairoh, Aminah; Ajat Rukajat; Yadi Fahmi Arifudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of Dhuha prayer habituation and its contribution to students' religious character at MTsN 9 Jakarta. A qualitative descriptive case-study design was employed. Data were collected through observation, semi-structured interviews with the madrasah principal, two teachers involved in the program, and two students, as well as documentation of schedules, facilities, and religious activities. Data were analyzed through data condensation, data display, and conclusion drawing; credibility was maintained through source, technique, and time triangulation. The findings show that Dhuha prayer has become an institutionalized religious culture implemented through a rotating schedule, teacher assistance, congregational prayer, collective supplication, and student-led short sermons. The program contributes to discipline, responsibility, worship awareness, politeness, honesty, and self-control, although internalization differs among students. Supporting factors include school policy, teacher exemplarity, clear task distribution, peer encouragement, and the availability of a mosque. Constraints include limited mosque capacity, damaged ablution facilities, student fatigue, and uneven willingness to participate without reminders. Facility improvement, systematic monitoring, contextual religious mentoring, and cooperation with parents are required to sustain the habituation process.